2004
DOI: 10.1016/j.jecp.2003.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A timing-specific memory distortion effect in young children

Abstract: It has been suggested that there are systematic distortions in childrenÕs memory for temporal durations, such that childrenÕs memory is not just less accurate than that of adults but qualitatively different. Experiment 1 replicated the memory distortion effect by demonstrating developmental change in the tendency to confuse a reference duration with one that is shorter rather than longer than it. When the long-term memory demands of the task were reduced by providing reminders of the reference duration on ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…There is wide agreement among researchers that duration is poorly understood by children and is inaccurately estimated before 8 to 10 years of age (Droit, 1995;Droit-Volet et al, 2001;McCormack, Gordon, Brown, Smith, & Brock, 2004). Most researchers have confirmed Piaget's (1927Piaget's ( /1971 prediction that children can infer event duration from nontemporal, perceptually based cues (succession, speed, and distance) only after 10 years of age, when they no longer confuse duration with distance or speed and understand the interrelationship among these three concepts (Acredolo, 1989;Levin, 1977;Levin, Israeli, & Darom, 1978;Matsuda, 2001).…”
Section: Durationmentioning
confidence: 99%
“…There is wide agreement among researchers that duration is poorly understood by children and is inaccurately estimated before 8 to 10 years of age (Droit, 1995;Droit-Volet et al, 2001;McCormack, Gordon, Brown, Smith, & Brock, 2004). Most researchers have confirmed Piaget's (1927Piaget's ( /1971 prediction that children can infer event duration from nontemporal, perceptually based cues (succession, speed, and distance) only after 10 years of age, when they no longer confuse duration with distance or speed and understand the interrelationship among these three concepts (Acredolo, 1989;Levin, 1977;Levin, Israeli, & Darom, 1978;Matsuda, 2001).…”
Section: Durationmentioning
confidence: 99%
“…McCormack et al (2002) and McCormack et al (2004) examined whether the systematic age-related changes in reference memory function found in temporal perception would also occur when nontemporal stimuli were stored. McCormack et al (2004) compared the performance of children and adults on a classic temporal generalization task and on a pitch generalization task. In a further paper, McCormack and colleagues compared elderly and adult temporal and nontemporal perception using an identification task (McCormack et al, 2002).…”
Section: Temporal Versus Nontemporal Processing: Differences In Memormentioning
confidence: 99%
“…Several of these studies have used the generalization task that initially was employed for animals and humans adults (Clément & Droit-Volet, 2006;Delgado & Droit-Volet, 2007;Droit-Volet, 2002;Droit-Volet, Clément, & Wearden, 2001;Droit-Volet & Izaute, 2005;McCormack, Brown, Maylor, Darby, & Green, 1999;McCormack, Brown, Smith, & Brock, 2004;McCormack, Wearden, Smith, & Brown, 2005). In this task, the participants are presented with a number of examples of a standard duration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the generalization task, younger children exhibit lower sensitivity to time than do older children. In addition, some studies have suggested a change with age in the distributional pattern of same responses around the standard, with the gradients being skewed to the left in 5-and 6-year-olds, symmetrical in 10-year-olds, and skewed to the right in adults (Clément & Droit-Volet, 2006;McCormack et al, 1999McCormack et al, , 2004. However, this developmental trend from left to right asymmetry has not always been observed given that symmetrical gradients have also been obtained in 3-and 5-year-olds and right asymmetrical gradients have also been obtained in 8-year-olds (Delgado & Droit-Volet, 2007;Droit-Volet et al, 2001;Droit-Volet & Izaute, 2005).…”
Section: Introductionmentioning
confidence: 99%